Malaysian roadside tree species selection in urban setting from landscape practitioners perspectives / Ramly Hasan - Hasan, Ramly (2019)
Roadside trees as a part of urban green infrastructure have the potential to cope with some of these problems in urban environment, as they can provide an array of services such as shade provision and aesthetic creation. Unfortunately, roadside trees are also acknowledged to render disservices. Damaged road surface, pedestrian walkway and underground utilities are few instances of this. Granting that the types of services and disservices vary according to tree species, the selection of tree species is hence crucial: the selection of the wrong tree species to be planted at the wrong place can lead to significant environmental, social and economic consequences. This is where the role of landscape practitioners in local authority comes into play as they are authorised in the decision making of tree species selection. In 2014-2016, statistics reveal high public complaints of many roadside trees problems, which not only leave the local authorities worried, but also require them to yearly spend more than hundreds of thousands of Ringgit Malaysia, paying public compensations and maintenance costs. This thereby calls this research to develop a Malaysian roadside tree species selection model for reference to the local authorities.